2017
DOI: 10.1002/chem.201701295
|View full text |Cite
|
Sign up to set email alerts
|

PCR Incorporation of Polyoxometalate Modified Deoxynucleotide Triphosphates and Their Application in Molecular Electrochemical Sensing of Yersinia pestis

Abstract: Redox-labeled nucleotides are of increasing interest for the fabrication of next generation molecular tools and should meet requirements of being thermally stable, sensitive, and compatible with polymerase-mediated incorporation while also being electrochemically discriminable. The synthesis and characterization of Keggin and Dawson polyoxometalate-deoxynucleotide (POM-dNTP) bioconjugates linked through 7-deaza-modified purines is described. The modified POM-dNTPs were used for polymerase-based amplification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…4 Nevertheless, the potential of hybrid POMs for cell targeting is yet undisclosed, and only a few bio-conjugates are known. [5][6][7] Among hybrid POMs, the Anderson-Evans [XMo 6 O 24 ] 3À polyoxomolybdates are disc-shaped polyanions of approximately D 3d symmetry, with average dimensions of 8.6 Â 8.6 Â 2.7 A. 8 Being oxidatively and hydrolytically stable, they are suitable for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…4 Nevertheless, the potential of hybrid POMs for cell targeting is yet undisclosed, and only a few bio-conjugates are known. [5][6][7] Among hybrid POMs, the Anderson-Evans [XMo 6 O 24 ] 3À polyoxomolybdates are disc-shaped polyanions of approximately D 3d symmetry, with average dimensions of 8.6 Â 8.6 Â 2.7 A. 8 Being oxidatively and hydrolytically stable, they are suitable for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…From the portfolio of our modified dNTPs bearing polyoxometalates, 54 benzofurazane, nitrobenzene, 55 , 56 and other electroactive substituents, we selected ferrocenylethynyl derivatives of dNTPs, which are available with all four nucleobases ( Figure 1 b). 49 51 , 57 , 58 …”
Section: Resultsmentioning
confidence: 99%
“…This may be attributable to a better substrate specificity of the Klenow (exo-) DNA polymerase for dA Fc TP as compared to dG Fc TP and dU Fc TP, as well as the possible steric hindrance between consecutive ferrocene-labeled bases at homopolymeric regions of the amplicon, which could inhibit the elongation at higher percentages of dN Fc TP, as was previously observed for other bulky electroactive labels. 54 …”
Section: Resultsmentioning
confidence: 99%
“…Several redox labeled dNTPs have been reported including ferrocene, 16 anthraquinone, 17 benzofurazane, 18 and polyoxometalates. 19 Ferrocene is particularly of interest because it is a reversible and stable label with redox peaks within the potential window of a gold electrode, and furthermore, Fc-labeled dNTPs are efficiently incorporated by several DNA polymerases such as Klenow (exo-), DyNAzyme, 16 and Vent (exo-). 20 We have chosen 7-ferrocenyl-ethynyl-7-deaza-dATP ( dA EFc TP ) because it was previously shown that 7-alkynyl-7-deazaadeninen are particularly good substrates for polymerases, even better than natural dATP.…”
Section: Introductionmentioning
confidence: 99%